Housing Rights for Wives After Divorce: A Comparative Analysis of Islamic Law and the Marriage Law - Putri Ayu Agustina; Jumni Nelli (Hakamain: Journal of Sharia and Law Studies, 2025)
The phenomenon of increasing divorce rates in Indonesia raises serious issues regarding the protection of women's rights, especially the right to housing after divorce, which is still often neglected in legal practice. Although a number of previous studies have discussed aspects of alimony, child custody, and division of joint property, there is still a gap in studies that specifically examine housing rights from a comparative perspective between Islamic law and Indonesian positive law. This study aims to analyse in depth the concept and implementation of housing rights for wives after divorce based on the Compilation of Islamic Law (KHI), the principles of maqāṣid al-syarī‘ah, and Law No. 1 of 1974 on Marriage, as well as to assess the extent to which the two legal systems can be harmonised. The method used is a qualitative approach with a comparative-normative method, through content analysis and legal literature review of legislation, Supreme Court decisions, and scientific works indexed by Sinta and Scopus. The results of the study show that Islamic law places the wife's right to housing as part of the protection of life and honour within the framework of maqāṣid al-syarī‘ah, while positive law interprets this right through the division of joint property as determined by the court. However, the lack of synchronisation in interpretation and implementation in the field has led to legal uncertainty, particularly in cases where the house is in the husband's name. Theoretically, this research broadens the understanding of the integration of Islamic values into the national family law system, while practically providing recommendations for policymakers and judicial institutions to formulate regulations that are more gender-responsive and based on substantive justice. These findings emphasise the urgency of harmonising Islamic law and national law in order to strengthen the protection of women's rights after divorce and ensure social justice in the Indonesian family law system